Kemampuan fag litik Listeria dalam menginfeksi Listeria grayi pada matrik udang: The abitity of Listeria lytic phage of infect Listeria grayi in shrimpi matrices - Rahmiati, Retnani; Rahayu, Winiati P; Budiarti, Sri; Kusumaningrum, Harsi D (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Shrimp belongs to type of food that oftenly contaminated with Listeria spp. Bacteriophage as an antimicrobial agent represents an attractive way to destroy bacterial contamination on food. This study presents the proof of lytic phage of Listeria (FL03) usage and influenced storage temperature to infect Listeria grayi on food matrix of shrimp. Shrimp samples were inoculated with 1.3 X 107 CFU mL-1 L. grayi (BA03) and then treated with 1.5 X 108 PFU mL-1 lytic phage of Listeria (FL03). The total number of L. grayi was counted at storage times of 0, 1, 24 and 48 hours at room temperature (±28 oC) and cold temperature (±4 oC). The results showed that shrimp treated with phage FL03 showed a decrease in the number of L. grayi compared to the control, namely 0 - 0.15 log10 CFU g-1 at room temperature (±28 oC) and 0.93 - 1.37 log10 CFU g -1 at cold temperatures (±4 oC). Treatment at cold temperatures (±4 oC) can inhibit the growth of L. grayi by 2.01 – 2.98 log10 CFU g-1. The growth inhibition of L. grayi increased further when treatment at cold temperatures (± 4 oC) was combined with FL03 phage treatment, namely to 3.38 – 3.76 log10 CFU g-1. These findings illustrated that phage FL03 could infect and cause lysis of L.grayi on food matrix of shrimp samples.